Statistics of magnetic reconnection in two-dimensional magnetohydrodynamic turbulence - Servidio, S. (2010)
The nonlinear dynamics of magnetic reconnection in turbulence is investigated through direct numerical simulations of decaying, incompressible, two-dimensional magnetohydrodynamics. Recently, it was shown by Servidio [Phys. Rev. Lett. 102, 115003 (2009)] that in fully developed turbulence complex processes of reconnection occur locally. Here, the main statistical features of these multiscale reconnection events are further described, providing details on the methodology. It is found that is possible to describe the reconnection process in turbulence as a generalized local Sweet-Parker process in which the parameters are locally controlled by the turbulence cascade, thus providing a step toward reconciling classical turbulence analysis with reconnection theory. This general description of reconnection may be useful for laboratory and space plasmas, where the presence of turbulence plays a crucial role. © 2010 American Institute of Physics.